2002
DOI: 10.1038/ng917
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution recombination map of the human genome

Abstract: Determination of recombination rates across the human genome has been constrained by the limited resolution and accuracy of existing genetic maps and the draft genome sequence. We have genotyped 5,136 microsatellite markers for 146 families, with a total of 1,257 meiotic events, to build a high-resolution genetic map meant to: (i) improve the genetic order of polymorphic markers; (ii) improve the precision of estimates of genetic distances; (iii) correct portions of the sequence assembly and SNP map of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

94
1,605
12
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,562 publications
(1,728 citation statements)
references
References 23 publications
94
1,605
12
3
Order By: Relevance
“…40 This points to high LD over the region, which has already been reported by Ueda et al 7 Our results not only show this high LD but also that it persists across populations worldwide. Previous studies in other genes, such as PAH 41 or the PKLR-GBA gene region, 42 have shown a general pattern of moderate geographical structure of LD with higher values out of Africa and low values in sub-Saharan Africa.…”
Section: Ld Patternssupporting
confidence: 82%
“…40 This points to high LD over the region, which has already been reported by Ueda et al 7 Our results not only show this high LD but also that it persists across populations worldwide. Previous studies in other genes, such as PAH 41 or the PKLR-GBA gene region, 42 have shown a general pattern of moderate geographical structure of LD with higher values out of Africa and low values in sub-Saharan Africa.…”
Section: Ld Patternssupporting
confidence: 82%
“…We thus computed IBD for 342 'derivative' pedigrees (including 251 intact pedigrees, 51 reduced pedigree, and 40 newly derived pedigrees) for chromosome X multipoint analysis. For the autosomal markers, map distances were obtained from the Center for Medical Genetics (http://research.marshfieldclinic.org/genetics/) whenever available or estimated otherwise; map distances for the X chromosomes were obtained from DeCODE [40]. Marker allele frequencies were estimated from the genotypes of the study participants by simple allele counting; this method yielded allele frequency estimates very similar to those obtained by maximum likelihood estimation.…”
Section: Methodsmentioning
confidence: 99%
“…In general, we used the Marshfield map (http:// research.marshfieldclinic.org/genetics) with two exceptions: (1) If there was considerable disagreement between the Marshfield and deCODE maps, 54 we used our data set to resolve the marker order and distances; (2) If there was a large disagreement between the Marshfield map and our data set that could not be resolved, we used the distances provided in the deCODE map if possible, or if not we used our data set to estimate distances. On chromosome 2, the distance between D2S1326 and D2S2241 was almost twice as large, and the distances between markers D2S2241, D2S142 and D2S1353 were considerably smaller, in the deCODE map than in the Marshfield map.…”
Section: Genotypesmentioning
confidence: 99%